2019
DOI: 10.1073/pnas.1821752116
|View full text |Cite
|
Sign up to set email alerts
|

EBV infection is associated with histone bivalent switch modifications in squamous epithelial cells

Abstract: Epstein−Barr virus (EBV) induces histone modifications to regulate signaling pathways involved in EBV-driven tumorigenesis. To date, the regulatory mechanisms involved are poorly understood. In this study, we show that EBV infection of epithelial cells is associated with aberrant histone modification; specifically, aberrant histone bivalent switches by reducing the transcriptional activation histone mark (H3K4me3) and enhancing the suppressive mark (H3K27me3) at the promoter regions of a panel of DNA damage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…As AP-1 was also demonstrated to regulate DNMT1 expression for methylation of the E-cadherin promoter in the presence of LMP1, it is possible a cross-talk exists in which LMP1 enhances the expression of AP-1 through phosphorylation of H3Ser10 at the promoter of AP-1, providing sufficient AP-1 for JNK/AP-1 pathway to up-regulate DNMT1 (Figure 1). In addition, our previous ChIP-Seq study comparing two pairs of EBV-positive and -negative NPE cell lines illustrated that EBV infection dysregulated histone bivalent switches, showing reduction of H3K4me3 and gain of H3K27me3, to suppress DNA damage repair (DDR) gene expression in a methylation-independent manner (103). The same study further showed that over-expression of EBNA1 could inhibit the expression of DDR genes (103).…”
Section: Elevation Of H3k27me3 and The Modulation Of Gene Expression mentioning
confidence: 95%
See 1 more Smart Citation
“…As AP-1 was also demonstrated to regulate DNMT1 expression for methylation of the E-cadherin promoter in the presence of LMP1, it is possible a cross-talk exists in which LMP1 enhances the expression of AP-1 through phosphorylation of H3Ser10 at the promoter of AP-1, providing sufficient AP-1 for JNK/AP-1 pathway to up-regulate DNMT1 (Figure 1). In addition, our previous ChIP-Seq study comparing two pairs of EBV-positive and -negative NPE cell lines illustrated that EBV infection dysregulated histone bivalent switches, showing reduction of H3K4me3 and gain of H3K27me3, to suppress DNA damage repair (DDR) gene expression in a methylation-independent manner (103). The same study further showed that over-expression of EBNA1 could inhibit the expression of DDR genes (103).…”
Section: Elevation Of H3k27me3 and The Modulation Of Gene Expression mentioning
confidence: 95%
“…In addition, our previous ChIP-Seq study comparing two pairs of EBV-positive and -negative NPE cell lines illustrated that EBV infection dysregulated histone bivalent switches, showing reduction of H3K4me3 and gain of H3K27me3, to suppress DNA damage repair (DDR) gene expression in a methylation-independent manner (103). The same study further showed that over-expression of EBNA1 could inhibit the expression of DDR genes (103). It seems that EBV could dysregulate the histone modifications in the precancerous host cells to suppress the key cancer-related genes without the involvement of DNA methylation.…”
Section: Elevation Of H3k27me3 and The Modulation Of Gene Expression mentioning
confidence: 99%
“…EBV infection of nasopharyngeal epithelial cells reduced the transcriptional activation mark H3K4me3 and enhanced the suppressive mark H3K27me3 at the promoter regions of several genes, including 16 DNA damage repair genes. The reduced DNA repair ability in EBV-infected nasopharyngeal epithelial cells may play an important role in nasopharyngeal carcinoma [ 222 ]. Infection of B cells with EBV resulted in a loss of H3K9me3, H3K27me3, and H4K20me3, histone markers that are associated with histone condensation.…”
Section: Oncoviruses and Chromatin Remodelingmentioning
confidence: 99%
“…EBV induced chromatin changes can also be mediated by microRNA. The EBV protein EBNA2 was found to induce miR-146-5p, which targets KDM2 mRNA [ 222 ].…”
Section: Oncoviruses and Micrornamentioning
confidence: 99%
“…Latent viral proteins can also modify host chromatin, such as in the case of latent factors EBNA3A- and EBNA3C-dependent recruitment of PRC2 to deposit repressive H3K27me3 marks on host tumor suppressor genes [ 107 , 113 ]. In nasopharyngeal carcinoma cells, EBV infection has also been shown to be associated with loss of H3K4me3/H3K27me3 bivalency in the promoter regions of crucial DNA damage response genes, demonstrating a viral mechanism of host chromatin regulation that may drive tumorigenesis in the epithelium [ 114 ].…”
Section: Impact Of Host Epigenetic Machinery On the Viral Life Cyclementioning
confidence: 99%